INVESTIGATION OF THE EVOLUTION OF SABATH GENE FAMILY IN CASSAVA (Manihot esculenta) REVEALS ITS POTENTIAL ROLE IN GROWTH AND DEVELOPMENT - Van Hai, Tong; Thi Bao Ngoc, Luu; Quoc Trung, Nguyen; Huy Gioi, Dong; Duc Ha, Chu; Van Tien, Tran; Viet Hong, La; Thi Ngoc Quynh, Le; Thi Thanh Huyen, Tran (HNUE Journal of Science: Journal of Natural Sciences, 2024)
SABATH is one class of enzyme belonging to the class of methyltransferase, playing a crucial role in plant defense and stress response mechanisms. Despite its importance, no systematic analysis of the expansion of the SABATH gene family in cassava (Manihot esculenta) has been reported up to date. In this study, we investigated the SABATH gene family in cassava, revealing their random distribution across 18 chromosomes, with variable numbers of gene copies per chromosome. According to gene duplication analysis, five duplication events were identified, primarily segmental duplications, indicating their evolutionary significance. The Ka/Ks ratio analysis indicated that most duplicated genes are under negative selection, preserving their functions, while one pair showed signs of positive selection, suggesting adaptive benefits. Gene structure analysis showed diverse exon counts, primarily three or four. Expression profiling across 11 cassava tissues demonstrated tissue-specific expression patterns, with some genes highly or exclusively expressed in specific tissues such as root apical meristems, embryogenic calli, and fibrous roots, implying distinct functional roles in cassava growth and development. Overall, this study provides valuable insights into the evolution and functional diversity of the SABATH gene family in cassava and identifies candidate genes for further functional characterization.